2006
DOI: 10.1088/0957-4484/17/5/001
|View full text |Cite
|
Sign up to set email alerts
|

A versatile platform for nanotechnology based on circular permutation of a chaperonin protein

Abstract: A number of protein complexes have been developed as nanoscale templates. These can be functionalized using peptide sequences that bind inorganic materials or by fusion to binding or catalytic proteins. In order to integrate peptides and proteins into specific positions in a protein template, we used circular permutation to relocate the amino and carboxy termini of the polypeptide chain. Additional sequences can then be joined to the protein termini. This minimizes disruption of the protein structure and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 41 publications
(50 reference statements)
1
39
0
Order By: Relevance
“…4). As previously reported, the circular permutant was similar to the wild-type beta rosettasomes with the nine subunits clearly distinguishable in end views and the characteristic banded structure visible in side views (Paavola et al, 2006). The cohesin-containing double rings (Fig.…”
Section: The Structure Of Rosettazymessupporting
confidence: 78%
See 2 more Smart Citations
“…4). As previously reported, the circular permutant was similar to the wild-type beta rosettasomes with the nine subunits clearly distinguishable in end views and the characteristic banded structure visible in side views (Paavola et al, 2006). The cohesin-containing double rings (Fig.…”
Section: The Structure Of Rosettazymessupporting
confidence: 78%
“…In vivo, the native rosettasome consists of mixtures of three closely related subunits (alpha, beta, and gamma) in different ratios, depending on the growth conditions of Sulfolobus (Kagawa et al, 2003) but we have demonstrated that in vitro double rings can form from the beta subunit alone (Koeck et al, 1998). Furthermore, this ring-forming ability is retained even after significant mutations of the beta subunit (Paavola et al, 2006). Using a mutant beta subunit in which the termini were relocated by circular permutation to an exposed position on the apical domain, we fused the cohesin-2 module from the C. thermocellum CipA protein to the carboxyl terminus of the permuted beta subunit and transformed the beta double rings into a scaffold for dockerin-containing cellulases, as shown in Fig.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Nature itself provides a rich source of self-assembled nanoscale structures such as viruses, ribosomes and many other highly complex, supramolecular machineries. By combining molecular biology and recombinant protein expression, several self-assembled nanoscale structures derived from nature's repertoire have been prepared for nanobiotechnological applications, including virus-like particles (VLPs) [12,13], ferritin protein cages [14][15][16], heat shock protein cages [17][18][19] and other selfassembled protein cages, such as enzyme complexes [20], chaperones [21], and carboxysomes [22]. According to Lee and Wang [23], the following characteristics make bionanoparticles more attractive compared to synthetic nanoparticles: they have well organized architectures with a broad selection of sizes at the nanometer scale; they are monodisperse with uniform sizes and shapes; their three-dimensional structures can be resolved at atomic or near-atomic resolution; and they can be economically produced at a large scale in gram or even kilogram quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Although research on viruses and ferritin outweighs the other protein cages, new systems such as chaperones [5,17] and carboxysomes [18] have sprung up as possible alternative protein cages for bionanosciences. The characterizations of these systems are in much earlier phases compared to the preceding nanosystems of viruses and ferritin, but each individual system is a potential novel nanomaterial for future chemistries and genetic reprogramming.…”
Section: Bnpsmentioning
confidence: 99%